Green Accounting as a Control Tool Costs and Risks Environment Waste Medical in a Hospital - Stevanus Dewangga Giovani Vernon Imagoro; Ahmad Juanda; Driana Leniwati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The adoption of green accounting in the healthcare industry, particularly within hospitals, has become a crucial strategy to tackle the challenges of medical waste management, which carries serious health and environmental consequences. This research explores the role of green accounting as a mechanism for controlling costs and mitigating environmental risks associated with medical waste. Employing a descriptive qualitative method, data were obtained through interviews, observations, and document reviews in hospitals implementing eco-friendly waste management practices. Findings indicate that green accounting enables hospitals to better identify and allocate environmental expenses, enhance the efficiency of waste management, and increase transparency in reporting externality costs. Moreover, green accounting contributes to promoting sustainability-focused managerial decisions and adherence to environmental regulations. Therefore, incorporating green accounting principles into hospital management systems represents a strategic measure for controlling costs and minimizing environmental risks linked to medical waste.